What Types of Terms Do People Use When Describing an Individual’s Personality? - Leising, Daniel; Scharloth, Joachim; Lohse, Oliver; Wood, Dustin (Psychological Science, 2014)
An important yet untested assumption within personality psychology is that more important person characteristics are more densely reflected in language. We investigated how ratings of importance and other term properties are associated with one another and with a term’s frequency of use. Research participants were asked to provide terms that described individuals they knew, which resulted in a set of 624 adjectives. These terms were independently rated for importance, social desirability, observability, stateness versus traitness, level of abstraction, and base rate. Terms rated as describing more important person characteristics were in fact used more often by the participants in the sample and in a large corpus of online communications (close to 500 million words). More frequently used terms and more positive terms were also rated as being more abstract, more traitlike, and more widely applicable (i.e., having a greater base rate). We discuss the implications of these findings with regard to person perception in general.